A Gel/Fiber composite formulation achieves sequential delivery based on multimodal analgesia reducing chronic pain. (January 2023) - He, Yumiao; Sun, Fengrun; Li, Mohan; Ji, Tianjiao; Fang, Yehong; Tan, Gang; Ma, Chao; Huang, Yuguang
Graphical abstract: Highlights: Multimodal analgesia was combined with extended-delivery system for the first time. A composite Gel/Fiber system was synthesized to achieve sequential release of multiple drugs for stage-specific analgesia. Bupivacaine hydrochloride was released preferentially to relieve early-onset nociceptive pain. More sustained release of acetaminophen was designed to reduce gradually-induced inflammatory reaction. The composite successfully achieved chronic pain prevention in rat chronic constriction injury model. Abstract: Pain management plays an essential role in medical care. Previous studies showed that pain is a dynamic process involving multiple mechanisms, which inspired the concept of multimodal analgesia. Therefore, a drug delivery system loaded with a single analgesic may be insufficient for pain control. In this study, an implantable thermogel/electrospun fiber (Gel/Fiber) system loaded with bupivacaine hydrochloride (BUP-HCl) and acetaminophen (APAP) was synthesized. In the composite, BUP-HCl was preferentially released from the hydrophilic thermogel to relieve nociceptive pain, followed by the release of APAP in a more sustained manner from hydrophobic fibers to reduce the inflammatory reaction. Pain behavioral study and activation assay of spinal glial cells in the chronic constriction injury (CCI) model demonstrated the superior analgesic efficacy and chronic pain prevention property of the Gel/Fiber system. Furthermore, the composite exhibited satisfactory biocompatibility, as shown by histological and pharmacokinetic analysis. These results indicate that the successful sequential BUP-HCl/APAP release by a Gel/Fiber system alleviates chronic pain with good biocompatibility.Our study may pave the way for the future application of extended-delivery systems.